2014
DOI: 10.3354/meps10668
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between upper ocean layer variability and size-fractionated phytoplankton in a non-nutrient-limited environment

Abstract: We describe the coupling between upper ocean layer variability and size-fractionated phytoplankton distribution in the non-nutrient-limited Bransfield Strait region (BS) of Antarctica. For this purpose we use hydrographic and size-fractionated chlorophyll a data from a transect that crossed 2 fronts and an eddy, together with data from 3 stations located in a deeply mixed region, the Antarctic Sound (AS). In the BS transect, small phytoplankton (< 20 µm equivalent spherical diameter [ESD]) accounted for 80% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
1
16
1
Order By: Relevance
“…Sangrà et al, 2011Sangrà et al, , 2014. Although the presence of such oceanographic features has been reported within the BS, particularly with an emphasis on their influence on phytoplankton community structure variability (Sangrà et al, 2014), only the Peninsula Front was identified in the present work. The inability to observe both the Bransfield Front and mesoscale anticyclonic eddies in this work could be as a result of the low spatial resolution coverage that exceeded the mean local first baroclinic Rossby radius Table 3 Abundance ranges (minimum and maximum, cells L −1 ) of the main phytoplankton taxa on four cruises (2003, 2004, 2008 and 2009) of deformation (Rd) (~10 km; Chelton et al 1998).…”
Section: Phytoplankton and Environmental Factors: Spatial Variabilitycontrasting
confidence: 35%
See 3 more Smart Citations
“…Sangrà et al, 2011Sangrà et al, , 2014. Although the presence of such oceanographic features has been reported within the BS, particularly with an emphasis on their influence on phytoplankton community structure variability (Sangrà et al, 2014), only the Peninsula Front was identified in the present work. The inability to observe both the Bransfield Front and mesoscale anticyclonic eddies in this work could be as a result of the low spatial resolution coverage that exceeded the mean local first baroclinic Rossby radius Table 3 Abundance ranges (minimum and maximum, cells L −1 ) of the main phytoplankton taxa on four cruises (2003, 2004, 2008 and 2009) of deformation (Rd) (~10 km; Chelton et al 1998).…”
Section: Phytoplankton and Environmental Factors: Spatial Variabilitycontrasting
confidence: 35%
“…These contrasting, transitional waters were previously shown to generate a noticeable, physical gradient across the BS, composed by the Peninsula Front (close to the AP), the Bransfield Front (close to the SSI) and an inter-frontal anticyclonic eddy field between those fronts (e.g. Sangrà et al, 2011Sangrà et al, , 2014. Although the presence of such oceanographic features has been reported within the BS, particularly with an emphasis on their influence on phytoplankton community structure variability (Sangrà et al, 2014), only the Peninsula Front was identified in the present work.…”
Section: Phytoplankton and Environmental Factors: Spatial Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis remains speculative as the dispersal route would be opposite to the generally westward flowing currents in the Antarctic Sound. It can, however, not be ruled out due to the turbulent hydrographic conditions in the Antarctic Sound (Sangrà et al, 2014). Colonisation by larvae from the southeast and southern Weddell Sea via the Weddell Gyre is also possible but less likely because of the much longer distance between the source region and the Nachtigaller Hill.…”
Section: Epibenthos Communitiesmentioning
confidence: 99%